Impact of Augmented Reality via Mobile Technology on Student Performance in Physics Practicals Work - Ayaichi, Laila; Bouras, Nihal; Amaaz, Aziz; Mouradi, Abderrahman; El Kharrim, Abderrahman (International Journal of Interactive Mobile Technologies (iJIM), 2024)
The current study was conducted to investigate the effect of using augmented reality (AR) via mobile devices on students’ performance in practical physics work. The study involved 108 second-year bachelor students specializing in physics and chemistry at the Higher Normal School of Abdelmalek Essaadi University. In this experimental study, the students were divided into two groups: an experimental group and a control group. The results indicate that using AR via mobile devices positively impacts students’ performance in practical physics work and significantly reduces the time required for the experimental group to complete various experiments.